The Aids policy cycle in Western Europe: From exceptionalism to normalization - Rolf Rosenbrock; Doris Schaeffer; Francoise Dubois-Arber; Martin Moers; Patrice Pinell; Michel Setbon (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1999)
In every Western European country the occurrence of Aids has led to exceptional innovations in prevention, patient care, health policy and questions of civil rights. This exception can be explained not only by the fact that a health catastrophe was feared, but also civilizational harm in the field of civil rights. Despite national differences, this brought about similar exceptionalist alliances consisting of health professionals, social movements and those affected. With the failure of a catastrophe to arise signs of fatigue in the exceptionalist alliance and increasing possibilities of medical treatment, exceptionalism in Europe is drawing to a close. The paper elucidates specific aspects of each of the four roughly distinguishable phases in this process: Approx. 1981 - 1986: emergence of exceptionalism. The underlying reasons for exceptionalism are investigated in this paper. Approx. 1986 - 1991: consolidation and performance of exceptionalism. The paper investigates the exceptionalist policy model, more specifically some nationally different factors in the polity and politics that help to explain the different forms of policies. Approx. 1991 - 1996: exceptionalism crumbling, steps toward normalization. The forces driving the process of normalization are investigated. Since 1996: normalization, normality. The changes made in the management of HIV and Aids are elucidated using examples from the fields of health care, primary prevention and drug policies. Aids health-policy innovations, and their risks and opportunities in the course of normalization are investigated. Three possible paths of development are identified: stabilization, generalization and retreat. The chances of utilizing innovations developed in connection with Aids for the modernization of health policy in other fields of prevention and patient care vary from country to country with the degree to which Aids exceptionalism has been institutionalized and the distance of these innovations from medical/therapeutic events. The contribution made by European countries to containing the global Aids crisis is inadequate.
Keywords: 300